The Ancient Maori System of Land Tenures - Acheson, F O V (Victoria University of Wellington Law Review, 1999)
This article is a thesis written for the Jacob University Joseph Scholarship 1913, Victoria University College, Wellington, New Zealand. The author discusses the system of Maori land tenure and finds that the Maori possessed a definite system of land tenure that was universally recognised and almost habitually respected. Even with occasional resistance to the system, those customs were not materially affected, nor did it have any lasting effect on rights in land. The author also finds that "force" was somewhat frequently used as a means of commanding respect for rights in land, thus leading many people to mistakenly believe that "force" constituted the whole of Maori "law" and that their only law was a "Law of the Strong Arm". The author concludes that it remains for us to deal with a few of the ordinary customs under which land was actually held, leaving over the great bulk of these customs for future treatment.